2013
DOI: 10.1107/s1600536813012348
|View full text |Cite
|
Sign up to set email alerts
|

4′,4′,6′,6′-Tetrachloro-2-(6-methylpyridin-2-yl)-1H,2H-spiro[naphtho[1,2-e][1,3,2]oxazaphosphinine-3,2′-[1,3,5,2,4,6]triazatriphosphinine]

Abstract: The title compound, C17H14Cl4N5OP3, is a spiro-phosphazene derivative with bulky naphthalene and pyridine rings. The phosphazene and the six-membered N/O rings are in flattened-boat and twisted-boat conformations, respectively. The naphthalene ring system and the pyridine ring are oriented at a dihedral angle of 18.06 (8)°. In the crystal, weak π–π stacking between the pyridine rings and between the pyridine rings and the naphthalene ring system [centroid–centroid distances = 3.594 (2) and 3.961 (2) Å, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…For N/O-donor-type bifunctional reagents used for the reaction of hexachlorocyclotriphosphazene giving spiro derivatives, see: Beşli et al (2007); Işıklan et al (2010Işıklan et al ( , 2013. For bond-length data, see: Allen et al (1987).…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…For N/O-donor-type bifunctional reagents used for the reaction of hexachlorocyclotriphosphazene giving spiro derivatives, see: Beşli et al (2007); Işıklan et al (2010Işıklan et al ( , 2013. For bond-length data, see: Allen et al (1987).…”
Section: Related Literaturementioning
confidence: 99%
“…Data collection: APEX2 (Bruker, 2007); cell refinement: SAINT (Bruker, 2007); data reduction: SAINT; program(s) used to solve structure: SHELXS97 (Sheldrick, 2008); program(s) used to refine structure: SHELXL97 (Sheldrick, 2008); molecular graphics: ORTEP-3 for Windows (Farrugia, 2012); software used to prepare material for publication: WinGX (Farrugia, 2012) and PLATON (Spek, 2009). As a part of our ongoing investigation on the reaction of hexachlorocyclotriphosphazene, N 3 P 3 Cl 6 , with N/O donor type bifunctional reagents such as aminoalcohols (Beşli et al, 2007), aminophenols (Işıklan et al, 2010) and aminonaphthols (Işıklan et al, 2013), the title compound was synthesized and its crystal structure is reported herein.…”
Section: Data Collectionmentioning
confidence: 99%
“…It has been observed that N 3 P 3 Cl 6 and bifunctional reagents give spiro-, ansa-, bino-and open-chain (vibrational) products in the reactions. There is limited research on the reactions between N 3 P 3 Cl 6 and N-substituted amino alcohols (Begeç, 2022;Beşli et al, 2007;Chandrasekhar et al, 1984;Coles et al, 2004;Eçik et al, 2012;Işıklan, Sayın, et al, 2016;Işıklan et al, 2013aIşıklan et al, , 2013bIşıklan, Yıldırım, et al, 2016). Microwave-assisted synthesis is a new concept in the synthetic chemistry.…”
Section: Introductionmentioning
confidence: 99%